PENGARUH PIJAT OKSITOSIN TERHADAP PRODUKSI ASI PADA IBU POSTPARTUM - Ika Nur Saputri; Desideria Yosepha Ginting; Ilusi Ceria Zendato (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2019)
Newborns do not need any other intake besides breast milk, but not a few found postpartum mothers who give formula milk to their babies because milk production is little or not smooth, especially in the first days of life. The purpose of this study was to determine the effect of oxytocin massage on breast milk production in postpartum mothers. This type of research was pre-experimental with the One Group Pre and Post Test Design. The population in this study were all postpartum mothers in June at the Nining Pelawati Clinic in 2019. The sample in this study was postpartum mothers with inclusion and exclusion criteria totaling 10 people. ASI production data is taken using a measuring cup which is then analyzed. Based on the results of the Wilcoxon Signed Rank Test, the average postpartum maternal breast milk production before oxytocin massage was 9.90 while the mean postpartum maternal breast milk production after oxytocin massage was 13.50. There was a significant effect of oxytocin massage on milk production with p-value = 0.008 (p â‰¤ 0.05). It is recommended for health workers to be able to carry out oxytocin massage to increase milk production in postpartum mothers.